ANALYSIS OF THE READINESS OF ECONOMICS TEACHERS IN FACING ONLINE LEARNING DURING THE COVID-19 PANDEMIC (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
This study aims to describe the readiness of economics teachers to face online learning during the Covid-19 pandemic. This study uses a quantitative approach with an explanatory survey method. The research was conducted at Public Senior High Schools in East Belitung Regency involving 15 teachers spread across 5 schools. The data collection technique in this study used a survey technique with the Guttman scale. The data analysis technique used in this study was to calculate the percentage of data from each indicator, then the data from the percentage score was interpreted and each indicator was analyzed in depth. The results of this study indicate that the readiness of economic teachers to face online learning during the COVID-19 pandemic as a whole is in the ready category, which is 55.60%, but when viewed from the eight indicators for indicators of teacher ability in planning and designing online learning designs and the ability to manage the learning system online, the teachers are not ready yet. Therefore, evaluation is still needed to improve teacher readiness in order to make online learning effective.    Keywords: Economics Teachers’ Readiness, Online Learning, Covid-19 Pandemic